A Judge Is the Person Who Decides Who Sings Better: Children’s Comprehension of Legal Terminology - Sacau-Fontenla, Ana (Criminology, criminal justice, law & society, 2024)
Children in contact with the law are especially vulnerable to misunderstandings due to their lack of knowledge about judicial proceedings and contexts that are complex for their level of development. This study examined whether children understand legal terminology commonly used at Portuguese courts. Three hundred twenty-two Portuguese-speaking schoolchildren aged 6 to 13 years participated in this study and were randomly distributed into two groups. We asked the children to define a list of 18 legal terms (9 for each group), which were previously identified after analyzing 33 children’s statements in cases of alleged sexual abuse. Their answers were categorized into five categories that reflect the mistakes children made when defining legal terms and the different strategies used in this task. As expected in light of the results of previous works, our results show that children do not understand the legal terms used at court: 47.2% do not show comprehension about any of the 9 terms presented. No child has been able to define all of them correctly. Age and school grade show a significant relationship with the level of understanding. No differences were found based on gender and children's contact with justice. Findings have implications about a necessary adaption of courts to children.